Evaluation of cold snare polypectomy for small pedunculated (Ip) polyps with thin stalks: a prospective clinical feasibility study. (1st February 2022) - Arimoto, Jun; Chiba, Hideyuki; Tachikawa, Jun; Yamaoka, Kenji; Yamazaki, Dai; Higa, Airi; Okada, Naoya; Suto, Takuma; Kawano, Naoya; Niikura, Toshihiro; Kuwabara, Hiroki; Nakaoka, Michiko; et al.
Abstract: Background: Although the use of cold snare polypectomy (CSP) has spread rapidly, no prospective studies evaluating the safety of CSP for pedunculated (Ip) polyps have been carried out. Aim: We performed this study to provide an accurate evaluation of the safety of CSP for Ip polyps. Methods: This is a prospective study (UMIN000035687). From January 2019 to February 2021, the safety of CSP for use on Ip polyps <10 mm with thin stalks was evaluated at our hospital. The primary outcome measure was the incidence of bleeding (delayed post-polypectomy bleeding (DPPB) and immediate bleeding). Results: During the study period, 89 consecutive patients (including 92 colonoscopies and 114 polyps) were prospectively enrolled. The en-bloc resection rate was 100%. The rate of DPPB after CSP was 0%, however, DPPB after conversion to HSP occurred in 1 case (33.3% (1/3)). The rate of immediate bleeding during CSP was 28.9% (33/114). Polyps with diameters ≥6 mm (OR (95% CI): 2.77 (1.041–7.376); p  = .041) were extracted as independent risk factors for immediate bleeding during CSP for Ip polyps. In all, 104 (91.2%) polyps were low-grade adenomas, and the percentage of cases with negative pathological margins was 96.5% (110/114). Conclusions: CSP for Ip polyps was safe and had good outcomes. We believe that Ip polyps could be included as an indication for CSP, and that CSP may become the next step in the 'cold revolution.' To confirm our results and verify CSP's inclusion in future guidelines, prospective, randomized studies are necessary.